Clinicopathological, Endoscopic and Radiological Evaluation of Intestinal Tuberculosis among Nepalese Patients at a Tertiary Care Center - Wangdi Sherpa, Tshering; Pathak, Rahul; Jha, Anurag (Europasian Journal of Medical Sciences, 2021)
Background: Intestinal tuberculosis is often difficult to diagnose due to its insidious onset and nonspecific and protean manifestations. Delay or failure of diagnosis is associated with significant complications like perforation, abscess, fistula and strictures. The objective of the study was to provide a descriptive analysis of clinical, endoscopic, radiological and pathological findings in these patients. Methods: A prospective study including 52 hospitalized patients was done between April 2018 to 2020 at Tribhuwan University Teaching Hospital. Statistical analyses were done by Microsoft excel version 16. Results: Males were 63% while females were 37%. The average age was 37 years. 84% had abdominal pain followed by abdominal distension (50%), chronic diarrhea (51%) and cough (21%). Abnormal chest X-Ray was found in (37%) among whom (53%) had sputum positive for tubercular Bacilli. Common CT scan findings were thickening and heterogenous enhancement of bowel loops (79%), lymphadenopathy (56%) and ascites (44%). Endoscopically, commonly involved sites were terminal Ileum (95%), cecum (77%) and ascending colon (42%). Frequent finding were ulcers (83%), patulous and deformed Ileocecal valve (33%), mucosal nodularity (38%), hypertrophic mucosa (21%) and strictures (11%). Biopsies revealed granulomas in (77%) specimens. (65%) of them had central caseous necrosis. Among 10 subjects undergoing needle aspiration of lymphnodes, (70%) had central caseous necrosis. Those with coexisting peritoneal involvement had a mean ascitic fluid adenosine deaminase level of 73 ± 8 IU/L. Conclusion: Intestinal tuberculosis remains a major concern in developing countries. A composite analysis of the clinical manifestations, CT scan, endoscopic findings and pathological examination of the biopsies aid in making a proper and timely diagnosis so as to prevent complications and mortality.